Multi-stakeholder data access in space-based climate monitoring - Kathryn Urban (Centre for International Governance Innovation (CIGI), 2024)
Data collected from satellite imagery and space-based instruments is essential to informing climate modelling. However, there is a fundamental tension between the public and private entities, who fund and maintain most of the data collection assets in orbit, and the civilian researchers, who seek to use that data to further our understanding of a changing climate. This paper puts forward a multi-stakeholder framework for climate data access, drawing out existing synergies across the public, private and scientific sectors to build on current climate data initiatives. This framework portends a leading role for defence actors owing to data requirements that mirror gaps in current researcher climate data access. The paper concludes with highlighting potential flashpoints in implementing the framework and makes recommendations for alleviating the concerns of key stakeholders.
Keywords: 330